Rebozo Technique and Nipple Stimulation on the Length of Labor in Period I in Maternity - Fauziandari, Erma Nur; Wulandari, Amri; Fijriyah, Saumi; Annarrahayu, Lutfi (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Childbirth is the process of movement of the fetus, placenta and membranes from the uterus through the birth canal. This process starts from the opening and dilation of the cervix caused by uterine contractions with regular frequency, duration, and strength. The Maternal Mortality Rate (AKI) in maternity reached 189 per 100 thousand live births, Indonesia ranked second highest in ASEAN. The cause of maternal death is 80% caused by direct factors (partus congestion, bleeding, eclampsia, sepsis, hypertension in pregnancy, and complications of abortion. To reduce AKI, pain management and appropriate childbirth care efforts are needed, namely pharmacological methods and non-pharmacological methods. The rebozo technique and nipple stimulation are non-pharmacological methods of complementary therapy in childbirth.Method: The purpose of this study is to determine the effectiveness of the rebozo technique and nipple pacifier stimulation on the duration of labor I. Type of experimental quantitative research with a case control design. The sampling technique in this study is purposive sampling, which is based on inclusion and exclusion criteria, with an independent t test and a sample of 27 maternity mothers, from PMB Saumi Fijriyah, PMB Kuswantiningsih, PMB Emi narimawati. The research period is from September to October 2024.Results: The results of the One Way Anova Analysis test obtained a significance value of α 0.119. Because the significance value α 0.119 > α 0.05, Ho was accepted and H1 was rejected, meaning that there was no significant difference in the length of time during labor in the Rebozo Technique, nipple stimulation group and the control group.Conclusion: The conclusion of this study is that there is no significant difference in the length of the first stage of labor in the Rebozo technique group, nipple stimulation and the control group because it is influenced by many factors.